2004
DOI: 10.1177/1077801203260948
|View full text |Cite
|
Sign up to set email alerts
|

Female Prostitution, Customers, and Violence

Abstract: Through a critical review of existing research, this article argues that (a) customers have been excluded from many debates surrounding prostitution, and including them will create a more robust dialogue regarding prostitution; (b) though prostitution seeking is often treated as a natural part of masculine sexual experience, most men do not pursue prostitutes, and very few are regular users; (c) many commonsense understandings of men's motivations for seeking prostitutes are consistent with existing research; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 54 publications
1
77
0
14
Order By: Relevance
“…This means that throughout their experience being trafficked, the trafficking victims came into contact with men who chose to pay for their services but did not provide a means of escape. Male customers may have their own personal reasons for keeping their exchange with a trafficking victim a secret; namely, they are engaging in an illegal activity (especially if they know or suspect the victim is a minor) by purchasing sex and they may wish to keep this activity from others in their life (Monto, 2004). The trafficking victim's customer enters their environment to touch, observe, and speak to them only to leave without providing help.…”
Section: Customersmentioning
confidence: 99%
“…This means that throughout their experience being trafficked, the trafficking victims came into contact with men who chose to pay for their services but did not provide a means of escape. Male customers may have their own personal reasons for keeping their exchange with a trafficking victim a secret; namely, they are engaging in an illegal activity (especially if they know or suspect the victim is a minor) by purchasing sex and they may wish to keep this activity from others in their life (Monto, 2004). The trafficking victim's customer enters their environment to touch, observe, and speak to them only to leave without providing help.…”
Section: Customersmentioning
confidence: 99%
“…Les travaux de Monto et de ses collaborateurs (Monto, 2000a(Monto, , 2000b(Monto, , 2004(Monto, , 2010Monto & Hotaling, 2001;Monto & McRee, 2005;Monto & Milrod, 2013) ont, quant à eux, identifié de petites différences, « en degré et non en qualité » (Monto & McRee, 2005, p. 505, ma traduction) entre les hommes arrêtés alors qu'ils tentaient d'obtenir les services d'une prostituée de rue et les hommes d'un échantillon national. D'une part, les clients arrêtés sont proportionnellement plus souvent célibataires ou moins heureux dans leur mariage et, d'autre part, ils présentent plus souvent des attitudes sexuelles plus libérales.…”
unclassified
“…Joseph & Black (2012) ont également noté, à la suite d'une étude quantitative des profils de clients, que « la marchandisation du sexe n'est pas inextricablement liée à des perceptions négatives envers les femmes [et qu'il nous faut] déconstruire le lien essentialiste entre la consommation du travail du sexe et le désir qu'aurait ces hommes d'exercer une domination sur les femmes » (p. 503, ma traduction) puisque ce ne sont pas tous les clients qui présentent une attitude inacceptable envers les travailleuses du sexe. Au contraire, la très grande majorité des clients agissent correctement vis-à-vis de celles-ci et la violence subie par les travailleuses du sexe est le fait d'un très petit nombre d'hommes violents (Kinnell, 2006;Klein et al, 2009;Jeffrey & MacDonald, 2006;Lowman & Atchison, 2006;Monto, 2000bMonto, , 2004Monto, , 2010Oerton & Phoenix, 2001;Parent & Bruckert, 2005;Sanders, 2008). Il arrive http://cgjsc-rcessc.uwaterloo.ca toutefois que des clients, par ailleurs non violents, adoptent un comportement agressif en réaction à un comportement vicitimisant de la part de la travailleuse du sexe, celle-ci ne donnant pas le service pour lequel elle s'est fait payer ou lui volant un bien.…”
unclassified
“…Diverse motivations for this conduct have been shown: a) some men want to enjoy different or more frequent sexual practices than usually available from their partners and go to persons practising prostitution because this may be the only way to obtain this (Monto 2001;McKeganey 1994); there are men for whom having sex with a prostitute is one of their sexual fantasies, as they are seen and perceived as super-sexual women who enjoy sex, giving rise to attraction or curiosity (Månsson 2006;Di Nicola et al 2009); c) for other men is it a quicker, more direct and less complicated way of obtaining sexual services, involving less commitment and emotional implication, given that standardised relationships require greater effort (xantidis et al 2000;Monto 2004;Pitts et al 2004;Campbell and O'Neill 2006); d) in other cases, prostitution allows men to have sex with different people, choosing different characteristics in the people who offer the services, such as ethnicity, physical attributes, sex or gender (McKeganey 1994;xantidis et al 2000); e) other clients find the illicit and clandestine nature of the sexual meeting attractive, either because it is a conduct that is socially reprehensible or because it is penalised in some countries (Månsson 2006); f) it has also been shown that some men have no other way of obtaining sex unless they pay for it, either because they do not have a partner, or because they have some problem that impedes them establishing relationships with, or because they are rejected by, women (Campbell and O'Neill 2006); in this context, personal deficiencies, scarce capacity or ability to engage in relationships with a partner have been alluded to (Atchinson et al 1998); g) in other studies it has been indicated that for some men prostitution is an alternative to solitary sexual activity, such as masturbation; that is to say, they have no other possibilities of having sex (Campbell and O'Neill 2006); h) some men seek in prostitution a way of maintaining control in their sexual relationships, or it can be a way of expressing their power over women (Atchinson et al 1998;Monto 2004;Campbell and O'Neill 2006); i) another of the reasons is that prostitution offers a less complicated form of extramarital relations, and can be experienced by men as a lesser infidelity, as there is no commitment to the people who are offering the sexual services (Månsson 2006); j) finally, it has been indicated that there are men who feel lonely, whether they be single or married, and besides the sexual services, they are seeking companionship and relationships of love or friendship with the people who practise prostitution (Monto 2004). It is possible...…”
Section: Introductionmentioning
confidence: 99%